Mode III stress intensity factors for cracked FGM rectangular plane. (May 2015) - Faal, R.T.; Dehghan, A.A.
Highlights: The stress field of the Volterra-type screw dislocation in FGM rectangular planes has a Cauchy singularity. The SIF of the crack tip in the FGM plane increases as it approaches the stiffer portion of the plane. Receding of the crack tips from the loading can decrease the normalized stress intensity factor. Abstract: Stress analysis is carried out in a rectangular plane made of functionally graded material containing a screw dislocation under anti-plane conditions. The elastic shear modulus of the rectangular plane varies continuously in the transverse direction. The resultant dislocation solution is used to derive a set of Cauchy singular integral equations. The corresponding solution to these equations is used to determine stress intensity factors for cracks. Several single-crack examples are solved. Furthermore, the interaction between two vertical and horizontal cracks as well as between two arc cracks is studied where the problem of two arc cracks will be re-examined by replacing one of them with an oblique straight crack.